Pemberdayaan Nelayan Melalui Pendekatan Sosial Ekonomi di Kecamatan Bantan Kabupaten Bengkalis - Juliana; Simbolon , Domu; Darmawan, Darmawan; Rumanti Kurniawati, Vita (Jurnal Kelautan, Lingkungan, dan Perikanan, 2025)
The government of Bengkalis Regency has yet to empower the fishermen in the fishing center of Bantan District according to the fishermen's expectations. Bengkalis Regency through Fisheries Office still have difficulty in developing fishermen empowerment strategies that are in line with fishermen's expectations. The existing empowerment strategies does not take into account the socio-economic aspects of fishermen, so fishermen are not encouraged to adopt advanced fishing technology. The purpose of this research is to identify and study the socio-economic aspects of fishermen to understand why they reluctant to adopt advanced fishing technology. This research was conducted in the fishing centers of Pambang Pesisir and Selat Baru Village. Data were collected through in-depth interviews with representative respondents such as fishers, fisheries extension workers, and officers from Fisheries Office. Descriptive analysis was conducted by taking into account the causal factors that will be used to formulate strategies to empower fishermen in the application of fishing technology by taking into account the socio-economic aspects that influence it. The goal to be achieved is for the fishermen to believe in and be willing to adopt more advanced technology. The socio-economic aspects that most influence the adoption of advanced technology are obedience to local authority and availability of capital. The Bengkalis district government's strategy is to reactivate the savings and loan cooperative while facilitating professional management, and the government is working with the village head and Atok (local leader) to gain the fishermen's trust in the empowerment efforts